CONVERSION OF HEAT ENERGY INTO ELECTRICAL ENERGY - Sharofiddinov Saydullo O‘ktamjon o‘g‘li; Mamasoliyev Xojiakbar Ne’matjon o‘g‘li; Raxmatullayev Shamsiddin Hakimboy o‘g‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: The conversion of thermal energy to electrical energy is currently being used on a large scale. As modern energy sources, we can support the conversion of thermal energy into electricity. The use of heat in technological and household appliances is carried out using various heating, heat supply systems. The technique of artificial frost formation also plays an important role in the thermal technique.